Monitoring and Analysis of Coastline Changes in the Coastal Area of Bali Island, Indonesia - Ni Nyoman Pujianiki; I Made Aryatirta Predana; Komang Gede Putra Airlangga; Gede Rai Putra Arya Simpangan; Takahiro Osawa; I Nyoman Sudi Parwata; Muhammad Shazril Idris Bin Ibrahim (Civil Engineering Dimension, 2024)
Erosion and accretion occuring in coastal areas are indications of changes in the coastline’s position. The beach areas in Bali have high economic value as tourist attractions; yet, the condition of the beaches in several places on the island is very concerning. Monitoring shoreline changes can be accomplished using remote sensing technology which is more efficient than the conventional methods. This paper describes the results of changes in the coastline from 2014 to 2021 with remote sensing for all coastal areas of the island of Bali surveyed in the field. This research has successfully detected changes in coastlines throughout the coastal areas of Bali Island by remote sensing method and verified by field survey. The survey results also show that remote sensing method has met the survey from previous studies specifically in Gianyar Regency and Jembrana Regency. Hence, it is applicable for further use in other areas.